The weight of history, territory and identity in the accession to the European Union - Vesna Lukovic (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2024)
Purpose: The aim of the study is to explore the current enlargement dynamics of the European Union (EU) from the perspective of history, territory and identity. By looking at these issues in different country/case examples, the aim is to shed new light on why some enlargement processes have moved very slowly and how that compares to the current enlargement dynamics, taking into account new candidate countries from 2022. Design/methodology/approach: The study uses qualitative and explanatory approach. The method of inquiry is qualitative because it is focused on particular legal, political and social phenomena that cannot be captured by quantitative methods. That includes the question of minorities, their language, their national identities and the issue of territory "belonging" to a certain identity. Findings: The study finds that despite formal legal, economic, institutional and other requirements that candidate countries must achieve in order to join the EU, the current enlargement round is being affected by geopolitical considerations as never before. This has produced certain questions about relevant processes and brought to light some deep and unresolved issues between certain candidate countries and current EU members. Research limitations/implications: The analysis is based on legal texts and institutional country and other reports by the EU authorities and other international organizations and bodies. The research would benefit from additional sources, particularly from interviews with higher policy makers at the EU level in the current political setting following the European elections in June 2024. Originality/value: The originality of this study lies in its innovative approach to this theme. The value added is the examination of the current EU enlargement round from a particular viewpoint which has been largely neglected in research works on enlargement. This is particularly relevant in the context of the current geopolitical environment which has opened a plethora of processes, questions and decisions on EU enlargement that were unimaginable just a couple of years ago.
Keywords: P29; P50; 330; History; identity; language; EU accession; Ukraine